(untitled) (Economics and region, 2025)
Globalization, the digitalization of the economy, and an increase in cyber threats present new challenges for enterprises, necessitating the implementation of comprehensive strategies to integrate various aspects of economic security. The economic security of an enterprise can be examined at different levels of management, which include strategic, tactical, and operational management. At the strategic level, an enterprise should establish clear policies to address security concerns across all areas, particularly those risks that arise from global changes. Key tasks at this level include identifying potential threats that could negatively impact business operations and developing a human resources policy to ensure that staff are adequately trained to respond to these threats. Tactical management of economic security involves developing and implementing security systems and mechanisms that align with the established policies. This requires the involvement of experts to assess the necessary resources, create security plans, and monitor their effectiveness. A critical aspect of this level is the establishment of a training system for staff, as maintaining an adequate level of security hinges on the skills and knowledge of employees. At the operational level, it is essential not only to execute the planned strategies but also to continually monitor their implementation and respond promptly to any errors or emerging threats. This management level includes the development of appropriate procedures and regulations to ensure the smooth functioning of the enterprise and facilitate quick responses to potential incidents. Therefore, the creation of economic security policies must consider the needs of users and participants in management processes at all three levels: strategic, tactical, and operational. A well-designed framework for managing economic security not only enhances the enterprise’s protection but also strengthens its resilience against external and internal challenges. This approach can lead to the successful development of business processes, ensuring asset preservation and the company’s long-term competitiveness in the market.